Emergence and development of Physalis L. seedlings under colored shade nets and full sunlight - Silva, Daniel Fernandes da; Villa, Fabiola; Piva, André Luiz; Klososwki, Elcio Silvério; Mezzalira, Eder Junior (Revista de Ciências Agroveterinárias, 2020)
The objective of this paper was to evaluate the effect of the 50% colored shading on the emergence and development of seedlings of three Physalis species. The experimental design used was a completely randomized block design with subdivided plots and four replicates. The treatments consisted of screens providing 50% shading and four colorations, as well as cultivation in full sunlight. The subplots consisted of three species of Physalis. Seeding was carried out in tubes and thinning was performed 40 days after sowing. During this period, the phytotechnical and physiological variables were evaluated. Plant emergence was favored by the screens. The cultivation environments interacted with the species regarding the emergence speed index, collar diameter, plant height, dry leaf biomass, and seedling transpiration rate. The environments did not interfere with the net assimilation rate, active photosynthetic radiation, SPAD index, dry root, stem and leaf biomass, and number of leaves per plant. The shading screens interfered with the air temperature and relative air humidity, as well as with a few phytotechnical characteristics. The use of a black shading screen provided a higher quality seedling.